NANOPARTÍCULAS DE CITRATO DE PRATA INCORPORADAS NO VIDRO TeLi VISANDO O AUMENTO DA EMISSÃO DO ÍON Te4+ - RODRIGUES, Lucas Limeira; CAPIOTTO, Adriana do Carmo; LIMA, Sandro Marcio; de ARRUDA, Gilberto José (ANAIS DO ENIC, 2023)
-